Medial Neck Femoral Fractures: Algorithm of Treatment and the Use of F.G.L. ™ Memory Shape Stem - Calderazzi, Filippo; Ricotta, Agostino; Schiavi, Paolo; Ceccarelli, Francesco (Acta Biomedica Atenei Parmensis, 2014)
Background and aim of the work: We treat undisplaced or minimally displaced medial neck femoral fractures with screws in both young and elderly patients with good activity of daily living, without severe comorbidity. Total hip replacement is preferred in middle-advanced age, with good level of functional activity. Bipolar hemiarthroplasty is performed on patients who may require early mobilization to avoid deterioration due to existing comorbidities. Bipolar hemiarthroplasty with memory shape stem (F.G.L.™) is our preferred mode of surgery for high risk patients (ASA classification). In fact, higher perioperative mortality from cardiopulmonary complications has been attributed to the use of cement during arthroplasty. This stem in its metaphyseal region has 10 tabs, made of a Nitinol™ alloy, that facilitate the restoration of the implant to its original enlarged shape at physiological temperature. This enables a strong fit in the metaphyseal region. Methods: We report the clinical and radiological results of 24 patients (mean follow-up: 14 months) who underwent surgical procedure of bipolar hemiarthroplasty with F.G.L.™ stem in our department between March 2008 and December 2009. Results: No perioperative complications were observed and the results were comparable to those of patients who underwent standard cemented bipolar hemiarthroplasty. Conclusions: A significant advantage to the use of F.G.L.™ stem is that it allows immediate primary stability without using cement. A limiting consideration is the higher cost associated with the implant & procedure in comparison with standard cemented bipolar hemiarthroplasty. This implant may thus be most suitable for patients with pre-existing cardio-pulmonary complications for whom the use of cement is a major risk factor.